Microcalorimetry in Historical Aspect, Status and Prospects: Part II - Mykytiuk, P.D.; Mykytiuk, O.Yu.; Mykytyuk, O.P. (Journal of Thermoelectricity, 2025)
Part II of the article highlights the main applied areas of practical use of microcalorimeters of various types, including microcalorimeters with thermoelectric sensors. The role of microcalorimetric methods in materials science, pharmacy, biology and medicine, in the study of food products, for environmental monitoring, in astronomy and elementary particle physics is considered. The future of calorimetry is discussed, namely: areas of application and potential achievements that can be expected when integrating with artificial intelligence, in establishing a connection with other analytical methods that deepen the understanding of thermal phenomena, in the development and use of simulation models, and in improving miniaturization